2007
DOI: 10.1038/sj.leu.2404734
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib significantly impairs the immunostimulatory capacity of human myeloid blood dendritic cells

Abstract: Bortezomib is a potent drug for the treatment of multiple myeloma. Its anti-tumor activity is mediated by proteasome inhibition leading to decreased cell proliferation and induction of apoptosis. However, an unimpaired proteasomal function plays a crucial role for the induction of anti-tumor immunity by dendritic cells (DCs), which are currently used for therapeutic vaccination against various tumors including myeloma. In the present study, we investigated the impact of bortezomib on the immunostimulatory capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 51 publications
2
41
2
Order By: Relevance
“…Moreover, differently than in both reports, in our study monocytes were cultured with GM-CSF to prevent spontaneous apoptosis (36 ± 13%, n ¼ 5, data not shown). 21 As suggested by previous studies, 12,15 cytokines, such as GM-CSF and IL-4, might increase the sensitivity of monocytes to Bortezomib. Finally, Bortezomib appears to spare other leukocyte subpopulations, such as B and T lymphocytes, suggesting that it may be a selective inhibitor of the function and survival of cells belonging to the monocyte/DC lineage.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, differently than in both reports, in our study monocytes were cultured with GM-CSF to prevent spontaneous apoptosis (36 ± 13%, n ¼ 5, data not shown). 21 As suggested by previous studies, 12,15 cytokines, such as GM-CSF and IL-4, might increase the sensitivity of monocytes to Bortezomib. Finally, Bortezomib appears to spare other leukocyte subpopulations, such as B and T lymphocytes, suggesting that it may be a selective inhibitor of the function and survival of cells belonging to the monocyte/DC lineage.…”
Section: Discussionmentioning
confidence: 81%
“…[11][12][13][14] However, it is not known whether Bortezomib induces the apoptosis of 'native' DC circulating in the peripheral blood, although it may alter the function of circulating myeloid DC ex vivo. 15 Moreover, the effects of Bortezomib on monocytes have not been thoroughly investigated. Besides being a major source of DC both in vitro and in vivo, monocytes play a role in a variety of chronic inflammatory disorders, including Systemic Lupus Erythematosus 16 and Systemic Sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we demonstrated that activated slanDCs produce large amounts of tumor necrosis factor (TNF)-a, interleukin (IL)-1β, IL-6, IL-12 and IL-23, efficiently stimulate CD4 + and CD8 + T cells, and promote the polarization of naïve CD4 + T lymphocytes into Th1 or Th17/Th1 cells. [8][9][10][11] In addition, we found that the high proinflammatory capacity of slanDCs is retained after granulocyte-colony stimulating factor (G-CSF) treatment of peripheral blood stem cell donors.…”
mentioning
confidence: 99%
“…At the same time, pDCs also mature but do not migrate to MLN, and hence may act as local source of IFN-␣ to prime innate and adaptive immune response. Therefore, pulmonary delivery of known DC maturation inhibitors such as prostaglandin E 2 , Bortezomib, FK778, a derivative of the active leflunomide-metabolite, within the first 24 h after HD-Ad vector delivery, may inhibit priming of pulmonary adaptive immune responses by preventing maturation and thereby migration of cDCs (41)(42)(43). Moreover, because T cell proliferation peaked around a week after HD-Ad delivery, transient immunosuppression within a week after HD-Ad vector delivery using cyclosporine A or CTLA4Ig to inhibit CD28/B7 pathway or inhibition of CD40/ CD40L pathway via CD40LIg administration will prevent T cell proliferation, and hence suppress adaptive immune response to HD-Ad vectors (44 -46).…”
Section: Discussionmentioning
confidence: 99%